Evaluation of Tobramycin and Ciprofloxacin as a Synergistic Combination Against Hypermutable Pseudomonas Aeruginosa Strains via Mechanism-Based Modelling - Vanessa E. Rees; Jürgen B. Bulitta; Antonio Oliver; Roger L. Nation; Cornelia B. Landersdorfer (MDPI AG, 2019)
Hypermutable Pseudomonas aeruginosa strains have a greatly increased mutation rate and are prevalent in chronic respiratory infections. Initially, we systematically evaluated the time-course of total and resistant populations of hypermutable (PAO∆mutS) and non-hypermutable (PAO1) P. aeruginosa strains in 48-h static concentration time-kill studies with two inocula. Both strains were exposed to clinically relevant concentrations of important antibiotics (aztreonam, ceftazidime, imipenem, meropenem, tobramycin, and ciprofloxacin) in monotherapy. The combination of tobramycin and ciprofloxacin was subsequently assessed in 48-h static concentration time-kill studies against PAO1, PAO∆mutS, and two hypermutable clinical P. aeruginosa strains. Mechanism-based mathematical modelling was conducted to describe the time-course of total and resistant bacteria for all four strains exposed to the combination. With all monotherapies, bacterial regrowth and resistant populations were overall more pronounced for PAO∆mutS compared to PAO1. The combination of tobramycin and ciprofloxacin was synergistic, with up to 106.1 colony forming units (CFU)/mL more bacterial killing than the most active monotherapy for all strains, and largely suppressed less-susceptible populations. This work indicates that monotherapies against hypermutable P. aeruginosa strains are not a viable option. Tobramycin with ciprofloxacin was identified as a promising and tangible option to combat hypermutable P. aeruginosa strains.